The SARS-CoV-2 vaccination rate and hesitation in Shanghai older adults with dementia - Yang Yang; Jing Nie; Fei Sun; Jinghua Wang; Jianhua Chen; Ling Li; Meiqing Sheng; Sijie Yang; Lei Yu; Xia Li (Frontiers in Public Health, 2023)
BackgroundOlder adults, particularly those with dementia, are at the greatest risk for being affected by SARS-CoV-2. Despite the Chinese government’s efforts to encourage older adults to receive SARS-CoV-2 vaccines, the vaccination rate, especially among older adults with dementia, remains low.ObjectiveThis study aimed to examine the willingness and attitudes towards vaccination among guardians of older adults with dementia and to uncover the factors that may have influenced attitudes towards vaccination during the 2022 Omicron Variant of SARS-CoV-2 outbreak in Shanghai, China.MethodsWe conducted a cross-sectional study using self-administered anonymous questionnaires to guardians of dementia patients in three settings: psychogeriatric inpatient wards, long-term care facilities, and home settings from April to May 2022. The primary outcome was participants’ willingness to allow dementia patients to receive SARS-CoV-2 vaccines. Logistic regression analyses were used to identify factors associated with vaccination willingness.ResultsA total of 327 valid questionnaires were collected. The vaccination rate among participants from long-term care facilities (12.9%) was lower than those in the psychiatric ward (19.3%) or community-dwelling settings (27.1%) (p < 0.05). The guardians’ primary concern was that vaccination would aggravate the health conditions of dementia patients [adjusted odds ratio (OR) = 5.11; 95% confidence interval (CI): 1.86–14.05]. Additionally, negative reports about the vaccination [OR = 3.94; 95% CI: 1.68–9.24], and adverse reactions [OR = 2.50; 95% CI: 1.13–5.52] were related to higher odds of vaccine hesitancy.ConclusionOur results showed that low vaccination rates in older adults with dementia were mainly due to their guardians’ concerns about vaccine safety. Our findings first uncovered the actual SARS-CoV-2 vaccination rates among older adults with dementia and may provide potential interventions to reduce unjustified worries towards vaccination.